The political economy of green input subsidies in developing economies: Insights from Colombia - Mockshell, Jonathan; Hidalgo, Francisco; Ritter, Thea; Alvarez, Diego; Blanco, Maria (2025)
Political economy analysis of green input subsidies in Colombia reveals a complex landscape shaped by political and institutional dynamics, diverse stakeholder interests, and conflicting belief, value, and knowledge systems, resulting in both significant opportunities and constraints for transitioning to green inputs. Supporting a transition to sustainable agriculture requires balancing incentives that promote more efficient use of synthetic inputs and integrated management with those that encourage greater adoption of green inputs within agroecological approaches. Six programs are presented that boost the adoption of green inputs through subsidies, investments in infrastructure, training, and technical assistance. To achieve greater impact, these initiatives must be sustained and scaled up, supported by stronger private sector engagement, enhanced local capacities, and broader multistakeholder collaboration. Green input subsidies should be complemented by additional measures such as investments in infrastructure, research, local capacity development, and technical assistance, alongside taxing agricultural Green-house gas emissions and conditioning conventional subsidies on adherence to environmental and social responsibility practices.